Novel Foods and EU Law: Facing Ethical Lines - Niemiec, Ernestyna (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2023)
Although the EU regulations on novel foods came into force in the 1990s, the threat of a famine and food crisis in Europe has appeared to such an extent only in recent years. The concept of novel foods, which can address challenges, is nevertheless associated with several ethical issues. In the individual aspect, it is the possibility of using widely innovative methods to produce food that successfully replaces meat or provides an alternative to sugar. On a broader scale, it is a replacement of products that are too expensive for the environment (i.e., greenhouse effect, deforestation) to provide an additional, entirely separate source of nutrition. This paper seeks to answer the research question regarding the role of law in the process of developing the concept of novel foods, with particular reference to whether and how the law addresses the ethical challenges that are posed by the novel foods. In addition to the main conclusions (multi-faceted dimension of novel foods, ethical and moral barriers to overcome), future prospects are also presented.